1993
DOI: 10.1128/iai.61.10.4510-4513.1993
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin-induced synthesis of a Shiga-like toxin from enteropathogenic Escherichia coli H.I.8

Abstract: Escherickhia coli H.I.8, an 0128 infant diarrhea isolate, produces low titers of a unique Shiga-like toxin (SLT), called SLT-IIva, which is a variant of SLT-II. We investigated induction of toxin synthesis and the putative association of a bacteriophage with toxin synthesis. Induction of broth cultures of strain H.I.8 with mitomycin yielded a 3,000-fold increase in SLT-IIva, production of a colicin, and appearance of a bacteriophage. Southern hybridization demonstrated that the genes for SLT-IIva were not carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…It was suggested that the RecA protein plays a key role in the underlying mechanism of mitomycin-induced toxin expression. However, Yee et al (63) recently reported that mitomycin caused induction of a chromosomally encoded SLT-IIva in the enteropathogenic E. coli strain H.I.8 that was lysogenic with a non-toxin-carrying bacteriophage. Recently, Fujii et al (13) also reported encephalopathy in mice induced by the SLT-IIv-producing E. coli O157:H Ϫ strain E32411/HSC following mitomycin treatment.…”
mentioning
confidence: 99%
“…It was suggested that the RecA protein plays a key role in the underlying mechanism of mitomycin-induced toxin expression. However, Yee et al (63) recently reported that mitomycin caused induction of a chromosomally encoded SLT-IIva in the enteropathogenic E. coli strain H.I.8 that was lysogenic with a non-toxin-carrying bacteriophage. Recently, Fujii et al (13) also reported encephalopathy in mice induced by the SLT-IIv-producing E. coli O157:H Ϫ strain E32411/HSC following mitomycin treatment.…”
mentioning
confidence: 99%
“…Additionally, whole genome sequence analysis revealed the presence of phages l and SfII, as well as two additional prophages identified as Fels2 and phi4795, in the genome of E. coli MC185. To determine whether the prophages identified in E. coli MC185 could be induced, cells were exposed to different subinhibitory concentrations of mitomycin C, a potent prophage inducer (Mmolawa et al, 2002;Yee et al, 1993). After 1.5 h, a decrease in OD 600 was already observed at some concentrations of mitomycin C (i.e.…”
Section: Mitomycin C Induces Prophages Within E Coli Resulting In Cementioning
confidence: 99%
“…In this study, subinhibitory concentrations of mitomycin C and streptonigrin were used as inducers and were shown to effectively induce multiple prophages within E. coli, S. Typhimurium and S. Newport, and consequently led to cell lysis of the bacterial host. Mitomycin C, an antibiotic that inhibits DNA synthesis via intercalation and adduct formation (Iyer & Szybalski, 1963, 1964Tomasz & Palom, 1997), has been reported to be a potent prophage inducer capable of inducing a wide range of phages in various foodborne bacterial pathogens including E. coli, S. enterica serovar Typhimurium, L. monocytogenes, Vibrio vulnificus, Vibrio parahaemolyticus, Clostridium perfringens, Clostridium difficile, and Staphylococcus aureus among others (Cao et al, 2012;Gerner-Smidt et al, 1993;Gervasi et al, 2013;Horgan et al, 2010;Lan et al, 2009;Mmolawa et al, 2002;Pryshliak et al, 2014;Wallin-Carlquist et al, 2010;Yee et al, 1993). Streptonigrin is another antibiotic shown to induce prophages in bacteria (Levine & Borthwick, 1963;Muschel & Schmoker, 1966).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteriophages were induced from S . Infantis strains by methodologies described previously (Gemski et al , 1978; Miller, 1987; Yee et al , 1993). Briefly, 5 mL of an overnight brain heart infusion (BHI) broth culture was diluted 10 −2 with fresh BHI broth and incubated for 3 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%